Complete Genome Sequence of Weissella hellenica 0916-4-2 and Its Comparative Genomic Analysis - Panthee, Suresh; Paudel, Atmika; Blom, Jochen; Hamamoto, Hiroshi; Sekimizu, Kazuhisa (Frontiers in Microbiology, 2019)
Weissella genus from Leuconostocaceae family forms a group of Gram-positive lactic acid bacteria (LAB) that mostly reside in fermented foods and some have been isolated from the environment and vertebrates including humans. Currently there are 23 recognized species, 16 complete and 37 draft genome assemblies for this genus. Weissella hellenica has been found in various sources and is characterized by their probiotic and bacteriocinogenic properties. Despite its widespread importance, little attention has been paid to genomic characterization of this species with the availability of draft assembly of two species in the public database so far. In this manuscript, we identified W. hellenica 0916-4-2 from fermented kimchi and completed its genome sequence. Comparative genomic analysis identified 88 core genes that had interspecies mean amino acid identity of more than 65%. Whole genome phylogenetic analysis showed that three W. hellenica strains clustered together and the strain 0916-4-2 was close to strain WiKim14. In silico analysis for the secondary metabolites biosynthetic gene cluster showed that Weissella are far less producers of secondary metabolites compared to other members of Leuconostocaceae. The availability of the complete genome of W. hellenica 0916-4-2 will facilitate further comparative genomic analysis of Weissella species, including studies of its biotechnological potential and improving the nutritional value of various food products.